Less direct than you thought: Do teachers transmit math value to students through their cognitive support for understanding?. (December 2021) - Dicke, Anna-Lena; Rubach, Charlott; Safavian, Nayssan; Karabenick, Stuart A.; Eccles, Jacquelynne S.
Abstract: Students' valuing of subject domains is an important contributor to students' educational success. As one avenue to foster students' valuing, social-cognitive motivational theories suggest that teachers might transmit their value beliefs to students through their instructional strategies. Accordingly, the current study examined the transmission of teacher's math value to students' math value via the content-related instructional strategy of cognitive support as reported by teachers and students. Using a longitudinal dataset of 1429 students (51% males, 68% Hispanic) and their 26 teachers (48% female), manifest-latent multilevel regression analyses showed some indication that teacher's endorsement of math valuing for their students, but not their personal value beliefs, might be associated indirectly with class average students' interest value through teacher's provision of cognitive support. Furthermore, teacher's reported cognitive support was related to the class average of students' value beliefs through class average students' perceptions of cognitive support, highlighting the importance of students' perceptions. Highlights: Teacher endorsement of math valuing for their students predicts cognitive support. Teachers' cognitive support predicts student valuing via their students' perceptions. Classroom mathematics valuing is linked with students feeling cognitive support.